Patients who are admitted to the Department of Internal Medicine with a very low C-reactive protein concentration. (1st September 2021) - Feigin, Eugene; Levinson, Tal; Berliner, Shlomo; Zeltser, David; Itzhak, Shapira; Shenhar-Tsarfaty, Shani; Egoz, Eyal; Meilik, Ahuva; Goldiner, Ilana; Rogowski, Ori; Wasserman, Asaf
Introduction: C-reactive protein (CRP) is a marker commonly used in clinical practice as a reference for the inflammatory activity in vivo. Low levels are often associated with good health and lower risk for adverse outcomes. Patients and methods: We examined medical records of the last 6 years, of all patients admitted for hospitalization in internal medicine wards who had the first CRP measurement below ≤ 0.03 mg/L (detection limit). Diagnosis criteria and 7 days' survival were reviewed. Results: Out of 61, 590 total admissions to internal medicine wards, three hundred and thirteen patients had CRP equal to or lower than 0.03 mg/L (0.5%). Second CRP measurement revealed gradual increment up to 10.8 ± 35.4 mg/L. Four patients died within 7 days from admission. Discussion: Presentation to the internal medicine department with a very low concentration of CRP is highly unusual, but it does not exclude the existence of significant acute morbidities. Clinicians should take additional CRP tests before any conclusion is considered regarding the presence or absence of an inflammatory response.